Regional Head Discretion Against Disharmony Between the Head of Service and the Regional Secretary in Cianjur Regency: reviewed from Law No. 30 of 2014 concerning Regional Government - Arkhan Aditya, Audy; Darwati, Darwati; Ferdiles, Lucky (Blantika: Multidisciplinary Journal, 2024)
The legal authority given to public officials is the responsibility of the position as the head of the Regional apparatus to provide appropriate legal information. The purpose of this study is to understand the regulations related to the Discretion of the Regional Head of Cianjur Regency so as to create a harmonious, clean and free government from all forms of corruption. Normative Juridical is the chosen research method, through a field approach and analyzed based on theory and comparative. The results of this study conclude that Law No. 30 of 2014 on Local Government explains how to use common sense, the concept of the right to reason as a middle ground between the weaknesses of the legal system and legal opportunities. As a state that adheres to the doctrine of the welfare state, the rule of law can play the highest role in protecting people's welfare. As the Local Government Law does not specifically regulate the settlement of disputes between public officials, mediation is the main way to unify perceptions based on Law No. 8 of 2003 concerning Guidelines for Regional Apparatus Organization whose task is to support the leadership of local government through policies and the main task of assisting Regional Heads in managing local government infrastructure, finance, equipment and facilities. The general principle of good governance so that in rational decision making as a responsibility of the position and personal responsibility.